Enhancing high school students’ critical thinking skills through the flipped-guided inquiry learning model with concept mapping - Sulfahmi Mursalim; Susriyati Mahanal; Hendra Susanto (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Critical thinking is a key 21st century skill vital for students’ academic and professional development. Preliminary studies at SMA Negeri 1 Singosari indicate that students' critical thinking skills are moderate and need improvement. This study examines the effect of the flipped-guided inquiry learning (FGIL) model integrated with concept mapping on the critical thinking skills of 11th-grade students. A quasi-experimental design with a nonequivalent control group was applied, involving pre- and post-tests. The critical thinking test comprised six essay items evaluated using Ennis’s rubric. ANCOVA results (p < 0.05) demonstrated a significant difference in performance among the FGIL-concept map group, FGIL-only group, and guided inquiry group. The FGIL model with concept maps showed the most substantial improvement. These findings suggest the potential of integrating concept mapping into flipped-guided inquiry to enhance students’ critical thinking in biology education.Abstrak. Berpikir kritis merupakan keterampilan utama abad ke-21 yang sangat penting bagi perkembangan akademis dan profesional siswa. Studi pendahuluan di SMA Negeri 1 Singosari menunjukkan bahwa keterampilan berpikir kritis siswa tergolong sedang dan perlu ditingkatkan. Studi ini mengkaji pengaruh model pembelajaran inkuiri terbimbing terbalik (FGIL) yang diintegrasikan dengan pemetaan konsep terhadap keterampilan berpikir kritis siswa kelas 11. Desain kuasi-eksperimental dengan kelompok kontrol non-ekuivalen diterapkan, yang melibatkan tes pra dan pasca. Tes berpikir kritis terdiri dari enam item esai yang dievaluasi menggunakan rubrik Ennis. Hasil ANCOVA (p < 0,05) menunjukkan perbedaan yang signifikan dalam kinerja antara kelompok peta konsep FGIL, kelompok hanya FGIL, dan kelompok inkuiri terbimbing. Model FGIL dengan peta konsep menunjukkan peningkatan yang paling substansial. Temuan ini menunjukkan potensi mengintegrasikan pemetaan konsep ke dalam inkuiri terbimbing terbalik untuk meningkatkan pemikiran kritis siswa dalam pendidikan biologi.